Identification of Structural Features for the Inhibition of OAT3-Mediated Uptake of Enalaprilat by Selected Drugs and Flavonoids - Ni, Yao; Duan, Zelin; Zhou, Dandan; Liu, Shuai; Wan, Huida; Gui, Chunshan; Zhang, Hongjian (Frontiers in Pharmacology, 2020)
Enalaprilat is the active metabolite of enalapril, a widely used antihypertension drug. The human organic anion transporter 3 (OAT3), which is highly expressed in the kidney, plays a critical role in the renal clearance of many drugs. While urinary excretion is the primary elimination route of enalaprilat, direct involvement of OAT3 has not been reported so far. In the present study, OAT3-mediated uptake of enalaprilat was first characterized and the inhibition of OAT3 transport activity was then examined for a number of flavonoid and drug molecules with diverse structures. A varying degree of inhibition potency was demonstrated for flavonoids, with IC50 values ranging from 0.03 to 22.6 µM against OAT3 transport activity. In addition, commonly used drugs such as urate transporter 1 (URAT1) inhibitors also displayed potent inhibition on OAT3-mediated enalaprilat uptake. Pharmacophore and three-dimensional quantitative structure-activity relationship (3D-QSAR) analyses revealed the presence of a polar center and a hydrophobic region involved in OAT3-inhibitor binding. For the polar center, hydroxyl groups present in flavonoids could act as either hydrogen bond donors or acceptors and the number and position of hydroxyl groups were critical drivers for inhibition potency, while carboxyl groups present in some drugs could form ionic bridges with OAT3. The predicted inhibition potencies by CoMFA and CoMSIA were correlated well with experimental IC50 values. Taken together, the present study identified OAT3-mediated uptake of enalaprilat as an important mechanism for its renal clearance, which may be liable for drug-drug and herb-drug interactions. The established computational models revealed unique structural features for OAT3 inhibitors and could be used for SAR analysis of OAT3 inhibition. The clinical relevance of the inhibition of OAT3-mediated enalaprilat uptake warrants further investigation, particularly in populations where herbal remedies and drugs are used concomitantly.